Magazyn Informacyjny . no. 4, 1981 - Niezależne Zrzeszenie Studentów Politechniki Warszawskiej, [ed. Darosław Paszkiewicz, Adam Stelęgowski] (NZS, 1981)
Creation and circulation: For internal use; Contains annotated review of articles from foreign press